My doctor's bag (Dorling Kindersley New York, 2002)
Let's play doctor! This ideal first board book is a toy and a book combined! Shaped to look like the real thing, My Doctor's Bag is the perfect platform for learning and fun. With large, clear photographs and 15 press-out pieces made to look like medical instruments, this book helps children begin sorting objects into sets and allows them to explore imaginative role-playing